Analytical study of upper gastrointestinal endoscopy in patients of gallstones with dyspepsia - Malik, Mehnish; Bhimani, Zulekha; Panchal, Anuradha; Eswar, P. S.; Shah, Nidhi; Singh, Shivam (International Surgery Journal, 2024)
Background: The relationship between gallstones and dyspepsia is complex and not fully understood. This study aimed to analyze the use of upper gastrointestinal endoscopy as a pre-operative investigation tool in gallstone disease associated with dyspepsia. Methods: A prospective observational study was conducted among 100 patients with gallstones and dyspepsia at D. Y. Patil University School of Medicine, Navi Mumbai, over a two-year period. Demographic data, clinical presentations, endoscopic findings and treatment outcomes were analyzed. Results: The majority of patients (46%) were in the 41-50 age group, with a female preponderance (68%). Abdominal pain was the most common symptom (99%). Upper GI endoscopy revealed abnormal findings in 66% of patients, with gastritis (26%) being the most frequent abnormality. H. pylori infection was present in 75% of patients. Most patients (92%) underwent cholecystectomy, with 58% receiving additional H.PYLORI treatment. Symptom relief within 1-4 weeks was observed in 64% of patients. Significant associations were found between USG findings and treatment choice (p<0.001) and between USG findings and time for symptom relief (p<0.001). Conclusions: Upper GI endoscopy revealed a high prevalence of abnormal findings in patients with gallstones and dyspepsia. The significant associations between USG findings, treatment choice and symptom relief highlight the importance of comprehensive pre-operative evaluation in these patients. These findings suggest that upper GI endoscopy and H. pylori testing may be valuable in guiding management decisions for patients with gallstones and dyspepsia.